"Everyone has it, everyone uses it": The emergence of "publicness" through multiplication in dialogical networks. (February 2023) - Korenaga, Ron; Ogawa, Tom
Abstract: This paper explores news production as "participatory journalism" in which ordinary people directly participate via the Internet. While participatory journalism idealises citizens' and journalists' co-creation, there are said to be limitations such as loss of quality, which results from the insularism of participants. In this paper, we consider the example of a Japanese TV news programme as participatory journalism. The programme reports on the problem of "isolation in connection" — youth's persistent sense of loneliness despite keeping in touch with many people via online connections. However, the concept of "isolation in connection" presents different versions of the problem such as public projections of personal angst. Therefore, we adopted a combined methodological perspective, including membership categorisation analysis (MCA) and dialogical networks (DNs). Subsequently, we investigated how the programme participants made the problem accountable through categorical descriptions and discursive organisation of interactions among relevant actors in the course of programme sequences. Through this investigation, we elucidate how publicness emerges through the multiplication of personal discourse in the DNs and we consider how news production works through discursive practices in the Japanese milieu.